2019
DOI: 10.2147/ott.s225733
|View full text |Cite
|
Sign up to set email alerts
|

<p>CARF, As An Oncogene, Promotes Colorectal Cancer Stemness By Activating ERBB Signaling Pathway</p>

Abstract: IntroductionThe role of CARF, a calcium-responsive transcription factor, in colorectal cancer initiation and development is still unknown. Here, we report that CARF promotes colorectal cancer stemness through ERBB signaling pathway.Materials and methodsBoth colorectal cancer cell lines and primary cells were used in this study. The levels of target mRNA and protein in the cells were examined by qRT-PCR and Western blot. Gene manipulation was achieved by the lentivirus delivery system. Luciferase reporter gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…However, there is currently no study focused on the signi cance of ACOX1 and LITAF in human CRC, so they are worthy of further study. Furthermore, GSEA analysis revealed that all of these key mRNAs were signi cantly enriched in well-known tumorigenesis related pathways, such as JAK-STAT signaling pathway [58], TGF-β signaling pathway [59], ERBB signaling pathway [60], and VEGF signaling pathway [61]. These reports above partially improved the credibility of our research, and further research on the signi cance of the novel ceRNA network in CRC is valuable.…”
Section: Discussionsupporting
confidence: 51%
“…However, there is currently no study focused on the signi cance of ACOX1 and LITAF in human CRC, so they are worthy of further study. Furthermore, GSEA analysis revealed that all of these key mRNAs were signi cantly enriched in well-known tumorigenesis related pathways, such as JAK-STAT signaling pathway [58], TGF-β signaling pathway [59], ERBB signaling pathway [60], and VEGF signaling pathway [61]. These reports above partially improved the credibility of our research, and further research on the signi cance of the novel ceRNA network in CRC is valuable.…”
Section: Discussionsupporting
confidence: 51%
“…miR-486-5p promotes the expression of five genes with oncosuppressive role and thereby with a negative effect on the CSC phenotype: FZB [ 56 , 57 ], SMAD4 [ 58 , 59 ], NFATC1 [ 60 , 61 ], CDX2 [ 62 , 63 ] and EP300 [ 64 , 65 ]. On the other hand it inhibits the expression of further five genes with oncogenic and CSC-promoting roles: NRCAM [ 66 , 67 ], JUN [ 68 , 69 ], WNT10A [ 70 , 71 ], FZD8 [ 72 , 73 ], and NODAL [ 74 , 75 ]. Furthermore, miR-486-5p showed a positive effect on the expression of PLK1, involved with a proper cell division process [ 76 ] and with controversial behavior in cancer, in which it is described both as an oncogene [ 77 ] and an oncosuppressor [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…27 Therefore, the adipocytokine signaling pathway and fatty acid metabolism may be involved in KIRC progression. Increasing evidence have shown that the mTOR signaling pathway, 28 PPAR signaling pathway, 29 ErbB signaling pathway, 30 and insulin signaling pathway 31 are significant cancer-related pathways. Moreover, it has been found that DNA replication and P53 signaling pathway, highly correlated with the genesis and development of tumors, were enriched in high-risk group.…”
Section: Verification Of Seven Mirnas Expression Levels Between Paired Kirc and Adjacent Non-tumorous Tissuesmentioning
confidence: 99%